Pattern of dyslipidemia among patients with subclinical hypothyroidism and its relation with thyroid stimulating hormone - Akter, Nazma; Akter, Tangera (BIRDEM Medical Journal, 2021)
Background: The relationship between subclinical hypothyroidism (SCH) and dyslipidemia is still debatable about whether SCH is constantly associated with lipid disorder. The aim of this study was to assess the lipid abnormalities in patients with SCH and to evaluate the relation between thyroid stimulating hormone (TSH) and lipid profile. Methods: This cross-sectional observational study was conducted in outpatient department (OPD) of the Hormone and Diabetes Clinic at MARKS Medical College & Hospital in Dhaka, Bangladesh from May 2018 to October 2019. A total of 308 subjects (age 30 - 60 years) were included in this study using covenience sampling. Among them, 156 were diagnosed case of SCH, while 152 were euthyroid healthy individuals in control group (matched for age, gender and weight). Laboratory test included serum TSH and free thyroxine (FT4) and fasting lipid profile. Data were analyzed using SPSS version 18 statistical software. Results: In this study, dyslipidemia was more prevalent in patients with SCH compared to control group [p<0.001]. SCH group showed altered lipid profile i.e. significantly higher serum total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), triglycerides (TGs) and lower high density lipoprotein cholesterol (HDL-C) when compared with the euthyroid subjects [p < 0.05 for each]. Pearson’s correlation coefficient for the relationships between serum TSH and lipid level showed that TSH levels were positively correlated with TC, LDL-C, TG and negatively correlated with HDL-C in patients with SCH [p < 0.05 for each]. Conclusions: Dyslipidemia is a common feature in SCH compared to euthyroid controls. The study showed that TSH level was positively correlated with TC, LDL-C, TG and negatively correlated with HDL-C. SCH should be a matter for further investigation because dyslipidemia is associated with this thyroid disorder. BIRDEM Med J 2021; 11(3): 172-178